Smoke and Fire Detection in Videos - Ugale, Meena; Nunes, Abhilash; Dias, Leroy; Pereira, Shalem (International Journal of Computer Sciences and Engineering, 2015)
This paper presents a computer vision-based approach for automatically detecting the presence of fire and smoke in video sequences. Since the fire causes serious disasters, fire detection has been an important study to protect human life. In this paper, the system proposed the fire- smoke detection algorithm in video sequence. The system focuses on optimizing the flame detection by identifying gray cycle pixels nearby the flame, which is generated because of smoke and of spreading of fire pixel and the area spread of flame. The model uses different color model for both fire and smoke and also the model use fuzzy logic or fuzzy inference system (FIS) to detect fire pixels. These techniques can be used to reduce false alarm by giving the accurate result of fire occurrence along with fire detection methods. The color models are extracted using statistical analysis of samples extracted from different type of video sequence and images. The extracted models can be used in complete fire/smoke detection system which combines color information with motion analysis. The strength of using video in flame detection is the ability to monitor large and open spaces. The system also give the opportunity to adjust the system by applying different combination of fire detecting techniques which will help in implementation of system according to different sensitive area requirement.